2017
DOI: 10.1016/j.memsci.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterion-containing polymer additives for fouling resistant ultrafiltration membranes

Abstract: Fouling is likely the most important obstacle to the use of membranes in many applications, especially in those that the feed contains high concentrations of organics such as oil and biomacromolecules. Zwitterions, defined as molecules with equal numbers of positively and negatively charged functional groups, show excellent fouling resistance and hydrophilicity. These features can be incorporated into ultrafiltration (UF) membranes during their manufacture by blending a commodity polymer like polyvinylidene fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 76 publications
(122 reference statements)
3
68
0
Order By: Relevance
“…The spectra of pure copolymers, C‐SB2VP and C‐SBMA, are shown as the topmost spectra, and display almost identical features. Two characteristic peaks appear for both copolymers at around 1146 and 1724 cm −1 , corresponding to SO asymmetric stretch and OCO ester carbonyl stretch, respectively. In agreement with the literature, as‐spun fibers that contain PVDF display strong characteristic crystal peaks of β ‐phase (1275 cm −1 ), with weak α ‐phase (614 and 763 cm −1 ) and γ ‐phase (811 and 1234 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The spectra of pure copolymers, C‐SB2VP and C‐SBMA, are shown as the topmost spectra, and display almost identical features. Two characteristic peaks appear for both copolymers at around 1146 and 1724 cm −1 , corresponding to SO asymmetric stretch and OCO ester carbonyl stretch, respectively. In agreement with the literature, as‐spun fibers that contain PVDF display strong characteristic crystal peaks of β ‐phase (1275 cm −1 ), with weak α ‐phase (614 and 763 cm −1 ) and γ ‐phase (811 and 1234 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Oil Red O was purchased from Sigma Aldrich (St Louis, Missouri). Poly(MMA‐ random ‐SBMA) and poly(MMA‐ random ‐SB2VP) were synthesized using free radical polymerization following protocols found in previous studies . These two copolymers will be referred to by C‐SBMA and C‐SB2VP, which stand for “copolymer poly(MMA‐ ran ‐SBMA)” and “copolymer poly(MMA‐ ran ‐SB2VP)”, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal cations used for membrane preparation used were non-toxic, environment friendly and cheap [188][189][190][191][192][193][194]. Their results revealed that when metal cations are incorporated within GO, resulted membranes were flexible with metal cations having no effect on GO membranes mechanical stability.…”
Section: Role Of Graphene Oxide In Polymer Nano-composite Membranesmentioning
confidence: 99%